2016 Update of the Portuguese Recommendations for the Use of Biological Therapies in Children and Adolescents with Juvenile Idiopathic Arthritis - Santos, MJ (2016)
To provide evidence-based guidance for the rational and safe prescription of biological therapies in children and adolescents with juvenile idiopathic arthritis (JIAs) considering the latest available evidence and the new licensed biologics. Rheumatologists and Pediatricians with expertise in Pediatric Rheumatology updated the recommendations endorsed by the Portuguese Society of Rheumatology and the Portuguese Society of Pediatrics based on published evidence and expert opinion. The level of agreement with final propositions was voted using an online survey. RESULTS: In total, 20 recommendations to guide the use of biological therapy in children and adolescents with JIAs are issued, comprising 4 general principles and 16 specific recommendations. A consensus was achieved regarding the eligibility and response criteria, maintenance of biological therapy, and procedures in case of non-response, for each JIA category. Specific recommendations concerning safety procedures were also updated. These recommendations take into account the specificities of each JIA category and are intended to continuously improve the management of JIA patients.